Therapeutic supramolecular tubustecan hydrogel combined with checkpoint inhibitor elicits immunity to combat cancer. (December 2021) - Wang, Feihu; Su, Hao; Xu, Dongqing; Monroe, Maya K.; Anderson, Caleb F.; Zhang, Weijie; Oh, Richard; Wang, Zongyuan; Sun, Xuanrong; Wang, Han; Wan, Fengyi; Cui, Honggang
Abstract: The clinical benefit of PD-1/PD-L1 blockade immunotherapy is substantially restricted by insufficient infiltration of T lymphocytes into tumors and compromised therapeutic effects due to immune-related adverse events following systemic administration. Some chemotherapeutic agents have been reported to trigger tumor-associated T cell responses, providing a promising strategy to achieve potent immune activation in a synergistic manner with PD-1 blockade immunotherapy. In light of this, a localized chemoimmunotherapy system was developed using an anti-cancer drug-based supramolecular polymer (SP) hydrogel to "re-edit" the host's immune system to combat cancer. This in situ forming injectable aPD1/TT6 SP hydrogel serves as a drug-delivery depot for sustained release of bioactive camptothecin (CPT) and aPD1 into the tumor microenvironment, priming the tumor for robust infiltration of tumor-associated T cells and subsequently prompting a response to the immune checkpoint blockade. Our in vivo results demonstrate that this chemoimmunotherapy hydrogel provokes a long-term and systemic anticancer T cell immune response, which elicits tumor regression while also inhibiting tumor recurrence and potential metastasis. Graphical abstract: Image 1